BIOLOGICAL CHARACTERIZATION OF INSECT PESTS Spodoptera exigua Hubner ORIGIN NORTH SULAWESI - Utari Satiman; Marthy Taulu (Indonesian Biodiversity Journal, 2023)
One component of integrated pest control is biological control or biological control based on the bioecology of the pest by taking into account the results obtained and their long-term effects through ecology and economy. The success of controlling a type of pest requires studies on various factors that affect the life of a pest, namely biology, morphology, ecology, genetics, and evolution. Knowledge of the biology of a pest species will provide appropriate information in breaking the life cycle or making the surrounding environment not provide optimal carrying capacity so that the pest population can be suppressed below the economic threshold. Spodoptera exigua is a polyphagous insect pest that eats from many plant types. In the larval stage, this pest attacks more than 20 species of cultivated and wild plants. For over twenty years, the onion caterpillar S. exigua has been the main target for chemical control but is still the main pest on onion crops. Spodoptera exigua attacks occur throughout the year in North Sulawesi and are spread over a wide geographical range, allowing genetic differences within the species. Gene mutations cause the occurrence of genetic diversity in a species in a population. High genetic diversity in individuals in a population can be one inhibiting factor in successfully controlling a pest species. Increasing knowledge about the biology of a pest species is very important to understand its habits, reproductive ability, and distribution which will later be used to limit and control the pest population.